Advances in Technology and Management Proceedings of the 2012 International Conference on Technology and Management (ICTAM 2012), International Convention Center Jeju, Jeju-Island, Korea - Kim, Haenakon (Advances in Intelligent and Soft Computing,, 2012)
This book Advances in Technology and Management contains 116 full length papers presented at the International Conference on Technology and Management, held on June 12-13, 2012, Jeju-Island, Korea. The goal of ICTAM 2012 is to bring together researchers working in many different areas of technology and management to foster international collaborations and exchange of new ideas.   This volume can be divided into two sections on the basis of the classification of manuscripts considered. The first section deals with technology. The second section of this volume consists of management.